Carbon Dioxide Emission in The Aviation Industry and Its Economic Aspect on The Example of Short and Long-Distance Flight Routes - Bartlomiej DZIEWONSKI; Rafal FENC (Communications of International Proceedings, 2023)
Carbon dioxide emissions around the world are the most concerning emissions for the power industry in terms of allowance they need to buy to by able to emit it. It can become a key factor for the transport industry in the next years as well. Currently the price of emitted tone of carbon dioxide. For now it is not obligatory to pay fee for emitting CO2 and in this work it will be discussed how it would affect the aviation transport companies and possibly their customers if the fees were obligatory. The most occupied aviation routes for Polish city Warsaw were taken into account. The most travelled destination in Europe and overseas where the point of discussion. The amount of fuel burned during flight on these routes were calculated and the emitted amount of carbon-dioxide. Basing on the amount emitted it is discussed how big cost it would be for the airline and possibly for the passengers if the airline would have to pay the same emission fees as power industry.
Keywords: Carbon-Dioxide; Emission; Economic; Cost